Customer Decision: An Empirical Study on Sourcing Credit from Banks - NOOR, Sembiring (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
Many companies require external financial resources (including from the banking sector) to meet their operational needs or for their business development. Such financing in most cases comes in form of bank loans. As a commercial service sector, banking also carries out promotions to attract customers. This study seeks to establish the influence of product / service promotion both partially and or simultaneously in increasing customer demand for credit and other banking services in the Jakarta region of Indonesia. The study is conducted on 351customers and players in the banking sector in Jakarta region using methods of sampling and analysis of data and testing with the t-test and f-test. From the findings, there is a significant influence of product promotion on customer response.